Analysis of the relationship between traditional markets and commodities trade - Todorovska, Ana; Milev, Stefan; Vodenska, Irena; T. Chitkushev, Lubomir; Trajanov, Dimitar (Ss Cyril and Methodius University in Skopje, Faculty of Computer Science and Engineering, Republic of North Macedonia, 2023)
In a global world, no country, market, or economy is isolated and can function independently. Interconnectivity is a fundamental feature of economic systems, including both traditional financial markets and novel markets. This study aims to explore the relationships between traditional markets and commodities trade. We develop a methodology for analyzing the relationships between five stock market indexes (S&P500, Dow Jones, BSE, Hang Seng, FTSE) and three commodities (crude oil, natural gas, gold), based on multimodal publicly available datasets incorporating structured numerical and unstructured news and social network data. To find the existence of direc tional associations, we develop an Explainable ML model that first learns the dependencies between different assets and then explains them in a form understandable by humans. We apply our methodology to analyze connectivity networks between the assets and discuss our conclusions.
Keywords: stock market indexes, gold, crude oil, natural gas, networks, NLP, sentiment